PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND ROBIN PADA MATERI BANGUN DATAR SEGI EMPAT DI SMP NEGERI 3 PONTIANAK - Muthia, Nabila; Yusmin, Edy; BS., Dian Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research aimed to determine the effectiveness of the Cooperative Learning model in geometry subject in SMP Negeri 3 Pontianak. The research method used was pre-experimental design with the research design was used one shot study design. The study sample were 30 students from class VII B of SMP Negeri 3 Pontianak. From the results of the study it showed that the implementation learning with the Round Robin was good with an average of 3.4, the percentage of student’s learning activity was classified as very active with an average of 83,05%, the percentage of student’s learning outcome with an average 70% of students achieved minimal passing grade. It can be concluded that learning using the Round Robin Type of Cooperative Learning Model is not effective for class VII geometry subject in SMP Negeri 3 Pontianak. Keywords: Learning Effectiveness, Quadrangles Subject, Round Robin